The Influence Of Group Elderly And Agricultural Extension Workers On The Participation Of Group Members In Air Latak Village, Seluma Barat District, Seluma Regency - Risky Afandra; Nurzam Nurzam; Iswidana Utama Putra (Utami Publisher, 2026)
Agriculture is a vital sector for economic development and food security in Seluma Regency, Bengkulu Province. The local government actively supports this sector through various assistance programs (seeds, pesticides, agricultural machinery, and replanting) for farmer groups, such as those distributed by the Agriculture Office in Air Latak Village, West Seluma District. Farmer groups serve as formal forums for farmers to increase productivity, implement technology, and strengthen their bargaining position. To optimize the role of these groups, the leadership of the leader is crucial in leading, motivating, and coordinating activities, as well as bridging the interests of members with agricultural extension workers and government agencies. This study is titled “The Role of Farmer Group Leader Leadership and Agricultural Extension in Increasing Member Participation in the Tani Farmer Group in Air Latak Village, West Seluma District.” The purpose of this study is to analyze the influence of group leader leadership (X1) and agricultural extension (X2) on member participation (Y). This research used a quantitative approach with a total of 80 respondents who are active members of farmer groups. Data were collected through a Likert‑scale questionnaire and analyzed using validity tests, reliability tests, multiple linear regression analysis, t‑test, F‑test, and the coefficient of determination (R²).The results of the study show that Leadership of the farmer group leader (X1) has a positive and significant effect on member participation, with a regression coefficient of 0.341 and a significance value of 0.002 < 0.05. Agricultural extension (X2) has a positive and significant effect on member participation, with a regression coefficient of 0.427 and a significance value of 0.000 < 0.05. Simultaneously, both variables have a significant effect on member participation with an F‑test significance value of 0.000. The regression equation obtained is: Y = 8.142 + 0.341X1 + 0.427X2 The coefficient of determination (R²) is 0.584, meaning that 58.4% of the variation in member participation can be explained by group leader leadership and agricultural extension, while the remaining 41.6% is influenced by other factors outside this study.